2023
DOI: 10.1136/bmjopen-2022-066920
|View full text |Cite
|
Sign up to set email alerts
|

Differences in humble leadership and team performance in nursing: an online cross-sectional study

Abstract: ObjectivesThe current study measures the differences in humble leadership and team performance in nursing based on the sample’s characteristics.DesignA cross-sectional study.SettingIn 2022, the current study sample was recruited from governmental and private universities and hospitals using an online survey.ParticipantsA convenience snowball sample of 251 nursing educators, nurses and students was recruited.ResultsA leader’s humble leadership, a team’s humble leadership and overall humble leadership were at mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
(157 reference statements)
0
0
0
Order By: Relevance
“…These results agreed with El-Gazar et al (2022) (4) who revealed that staff nurses perceived that their nurse managers have moderate humility. As well as, Yang et al (2019) (36) and Mrayyan (2023) (37) found that nurses perceived a moderate level of humble leadership from their nurse managers.…”
Section: Resultsmentioning
confidence: 93%
“…These results agreed with El-Gazar et al (2022) (4) who revealed that staff nurses perceived that their nurse managers have moderate humility. As well as, Yang et al (2019) (36) and Mrayyan (2023) (37) found that nurses perceived a moderate level of humble leadership from their nurse managers.…”
Section: Resultsmentioning
confidence: 93%
“…In this regard, leaders must set the example by demonstrating humble behavior so that their followers observe, learn, internalize and then imitate their actions (Al Hawamdeh, 2022). According to the results of current research, humble leaders in the health-care context exhibit certain characteristics such as the observance of fairness and equality between doctors, nurses and patients (Mrayyan, 2023), no discrimination between them (Yeager and Bauer-Wu, 2013) and focusing on teamwork and encouraging doctors, nurses and patients to participate and collaborate (Al Hawamdeh, 2022; Foronda, 2020). Accordingly, for the development of leadership skills, it is necessary to strengthen these qualities and for this purpose, appropriate training courses can be implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Another area of research examines the impact of HL on positive attitudes and behaviors in the workplace such as organizational citizenship behavior (Ding et al , 2020), innovative work behavior (Al Wali et al , 2022; Yang et al , 2019), work performance (Mrayyan, 2023), proactive behaviors (El‐Gazar et al , 2022), work engagement (Yang et al , 2019), psychological capital (Qian et al , 2020), trust in the leader (Al Hawamdeh, 2022), affective commitment (Zhou et al , 2021), self-efficacy (Al Hawamdeh, 2022; Chu et al , 2022) and psychological empowerment (El‐Gazar et al , 2022). Our results indicated that employees who work with humble leaders are more likely to show positive work behaviors in the workplace.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations